A new contribution to Megasporoporia sensu lato: Six new species and three new combinations - Wang, Ya-Rong; Dai, Yu-Cheng; Liu, Hong-Gao; Vlasák, Josef; Buchanan, Peter; Yuan, Yuan; Wu, Ying-Da (Frontiers in Microbiology, 2022)
Megasporoporia sensu lato has recently been intensively studied in China and South America, and four independent clades representing four genera are recognized phylogenetically. In this study, more samples mostly from subtropical and tropical Asia, Oceania and East Africa are analyzed. A phylogeny based on a 4-gene dataset of sequences (ITS + nLSU + mtSSU + tef) has confirmed the presence of four genera in Megasporoporia sensu lato: Jorgewrightia, Mariorajchenbergia, Megasporia and Megasporoporia sensu stricto. Six new species, Jorgewrightia austroasiana, J. irregularis, J. tenuis, Mariorajchenbergia subleucoplaca, Megasporia olivacea and M. sinuosa, are described based on morphology and phylogenetic analysis. Three new combinations are proposed, viz. Jorgewrightia kirkii, Mariorajchenbergia epitephra and M. leucoplaca. So far 36 species of Megasporoporia sensu lato are accepted, and an identification key to these species is provided. In addition, the identification of Dichomitus amazonicus, D. cylindrosporus, and Megasporoporia hexagonoides is discussed.